THE REALIZATION OF TASK-BASED LANGUAGE TEACHING TO FOSTER STUDENTS’ SPEAKING FLUENCY IN VOCATIONAL SCHOOL CONTEXT - Eline Rozaliya Winarto; Fitri Aprianti (English Review: Journal of English Education, 2022)
The present study aims at scrutinizing the realization of task-based language teaching in fostering students’ speaking fluency in vocational school context. Four diverse tasks are administered to the students particularly: sequencing task, picture narration task, question and answer task, and problem-solving task. Twenty-eight eleventh grade students in one vocational school in Cirebon were selected as the participants. From twenty-eight students, six participants were chosen as the representatives whose speaking performance were scrutinized by considering at several linguistic aspects namely segmental errors, speech rate, and grammatical accuracy. The findings indicated that task-based language teaching fosters students’ speaking fluency. There was an improvement in terms of students’ speech production specifically rhythm, segmental, and speech rate aspect. The students also showed positive responses throughout the realization of task-based language teaching in respect of the various aspect of English pronunciation awareness. Furthermore, the result of observation in each meeting and students’ interview revealed that students’ participation in interacting in English was enhanced. This study suggests that the students need to be exposed and learn the different aspects of pronunciation to further enhance their speaking performance.